2019
DOI: 10.1016/j.tics.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Self-Agency and Self-Ownership in Cognitive Mapping

Abstract: The concepts of agency of one's actions and ownership of one's experience have proven useful in relating body-representations to bodily-consciousness. Here we apply these concepts to cognitive maps. Agency is defined as "the sense that I am the one who is generating the experience represented on a cognitive map", while ownership is defined as "the sense that I am the one who is undergoing an experience, represented on a cognitive map". The roles of agency and ownership are examined with respect to the transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 97 publications
3
51
0
Order By: Relevance
“…We observed coding of social network relations at the retrosplenial complex (RSC), a region related to spatial scene processing. The RSC is known to integrate egocentric and allocentric spatial information (Arzy and Schacter, 2019;Byrne et al, 2007). In accordance with this idea, we also observed here coding of 'egocentric' social information (self-referenced personal affiliation) and 'allocentric' social information (objective relations between others in the social network, irrespective of relation to the self) in the RSC.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We observed coding of social network relations at the retrosplenial complex (RSC), a region related to spatial scene processing. The RSC is known to integrate egocentric and allocentric spatial information (Arzy and Schacter, 2019;Byrne et al, 2007). In accordance with this idea, we also observed here coding of 'egocentric' social information (self-referenced personal affiliation) and 'allocentric' social information (objective relations between others in the social network, irrespective of relation to the self) in the RSC.…”
Section: Discussionsupporting
confidence: 88%
“…Additional studies of the medial parietal lobe have demonstrated that it represents relations between social group categories (Leshinskaya et al, 2017) and across events in time (Baldassano et al, 2017). Our findings here strengthen the idea that the brain's spatial processing system has a domain-general role, and is involved in mapping knowledge across space, time and the social domain (Arzy and Schacter, 2019;Behrens et al, 2018;Bellmund et al, 2018;Constantinescu et al, 2016;Epstein et al, 2017;Wheatley, 2013, 2015;Parkinson et al, 2014;Peer et al, 2015;Schafer and Schiller, 2018;Tavares et al, 2015).…”
Section: Discussionsupporting
confidence: 81%
“…Although it is theoretically possible, cognitive processes, as they appear to us, do not happen without a physical form (embodied), are not entirely undirected (enacted), and do not appear without a physical (extended) or sociocultural (embedded) context. It has, however, been argued that aspects of a given cognitive act theoretically may be reduced to a point at which it is temporally unextended ( Gallagher, 2000 ; Zahn et al, 2008 ; Arzy and Schacter, 2019 ). These conceptions run the danger of identifying the capacities of the cognizer purely by spatial properties.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, and somewhat counter-intuitively, current research has suggested that this experience of a coherent "embodied self" actually hinges on an interplay between different processes rather than on a single mechanism (Metzinger, 2004). Among the more influential theoretical dissections of self-consciousness are Antonio Damasio's distinction between the proto-self, core self, and autobiographical self along an axis moving from visceral and autonomic to cognitive processing (Damasio, 2012 and see also Gallagher, 2000), and the growing evidence that the sense of body ownership and the experience of agency over the body rely, at least partially, on distinct mechanisms such as sensory-motor contingencies and cognitive mapping (Arzy and Schacter, 2019;Tsakiris et al, 2007) .…”
Section: Introductionmentioning
confidence: 99%